Formulasi dan Uji Aktivitas Antioksidan Sediaan Lulur Body Scrub Ekstrak Daun Kelor (Moringa oleifera) dengan Metode DPPH: Pengabdian - Silvia Mawardani; Tiara Ajeng Listyani; Niken Luthfiyanti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Moringa leaves (Moringa oleifera) are rich in various components of active substances, namely tannins, steroids, triterpenoids, flavonoids, saponins, anthraquinones, and alkaloids. Moringa leaves also contain minerals, essential amino acids, antioxidants, and vitamins. The content of the moringa plant that is efficacious as an antioxidant was found in the leaves, namely the content of vitamin E. Antioxidants are substances that are able to prevent or delay free radical reactions that occur in the lipid oxidation process. This study aimed to determine whether moringa leaf ethanol extract could be made into body scrub preparations that met physical quality standards, to determine the antioxidant activity of moringa leaf extract body scrub preparations, and to determine the concentration of body scrub preparations that were best used as antioxidants. In this study, the DPPH method (1,1-diphenyl-1-picrylhydrazyl) was used, and the extraction method was carried out using the maceration method. The extract was formulated with concentrations of 15%, 25%, and 35%, respectively. The evaluations used in this study included organoleptic test, homogeneity test, pH test, dispersion test, irritation test, and hedonic test. The results of this study showed that the best formulation of moringa leaf extract body scrub (Moringa oleifera) was the 35% formula with an IC₅₀ value of 62.120 μg/ml, categorized as having strong antioxidant activity.